Lipid Body Dynamics in Shoot Meristems: Production, Enlargement, and Putative Organellar Interactions and Plasmodesmal Targeting - Veerabagu, Manikandan; Rinne, Päivi L. H.; Skaugen, Morten; Paul, Laju K.; van der Schoot, Christiaan (Frontiers in Plant Science, 2021)
Post-embryonic cells contain minute lipid bodies (LBs) that are transient, mobile, engage in organellar interactions, and target plasmodesmata (PD). While LBs can deliver γ-clade 1,3-β-glucanases to PD, the nature of other cargo is elusive. To gain insight into the poorly understood role of LBs in meristems, we investigated their dynamics by microscopy, gene expression analyzes and proteomics. In developing buds, meristems accumulated LBs, upregulated several LB-specific OLEOSIN genes, and produced OLEOSINs. During bud maturation, the major gene OLE6 was strongly downregulated, OLEOSINs disappeared from bud extracts, whereas lipid biosynthesis genes were upregulated, and LBs enlarged. Proteomic analyses of the LB fraction of dormant buds confirmed that OLEOSINs were no longer present. Instead, we identified the LB-associated proteins CALEOSIN (CLO1), Oil Body Lipase 1 (OBL1), Lipid Droplet Interacting Protein (LDIP), Lipid Droplet Associated Protein1a/b (LDAP1a/b) and LDAP3a/b, and crucial components of the OLEOSIN-deubiquitinating and degradation machinery, including PUX10 and CDC48A. All RFP-tagged LDAPs localized to LBs when transiently expressed in Nicotiana benthamiana. Together with gene expression analyzes this suggests that during bud maturation OLEOSINs were replaced by LDIP/LDAPs on enlarging LBs. The LB fraction contained the meristem-related actin7 (ACT7), ‘myosin XI tail-binding’ RAB GTPase C2A, a LB/PD-associated γ-clade 1,3-β-glucanase, various organelle- and/or PD-localized proteins. The results are congruent with a model in which LBs, motorized by myosin XI-k/1/2, traffic on F-actin, transiently interact with other organelles and deliver a diverse cargo to PD.